New concepts in wound treatment - Bermudez Cedeño, Gonzalo (Revista Universidad de Guayaquil, 1984)
The fundamental principles of skin solutions of continuity (wounds) are that all of them are contaminated to a certain extent, even if only by the normal flora of the skin, based on the fact that there are no patients without germs and that every infected wound is related to the magnitude of the initial bacterial inoculum and the success of the defense mechanisms, whether these are local or general, because the human being is not free of germs, even in a state of total health, the bacterial presence is constant. I have begun this work that I consider, due to its scope, to be a work of profound social interest and a goal for medicine in the year 2000, although in order to carry it out, we have had to prepare ourselves for the most tiring discussions, the most painful disappointments, the most offensive insults, and what is even worse, the presumptuous judgment of the ignorant; because we know that in the face of adversity and incomprehension, the kite rises against the wind.